New frontiers on evaluating heat strain and disturbances of water and electrolyte balance in tennis - Bergeron, M. F. (2000)
Playing tennis in the heat presents a number of physiological challenges to all players. Fluid and mineral losses can be extensive and decreased performance or ultimately one or more symptoms of heat illness can readily manifest the effects of continual heat strain. In response to heat cramps, nausea, and weakness, a 17-year old, nationally ranked tennis player drank an excessive amount of water, after playing a 4-hour tournament match in the heat (>38°C). Subsequently, in his hotel room, this player had a seizure, slipped into a coma, and spent 2 days in the hospital, before he recovered and his serum electrolytes were stabilized. His first measured serum sodium level was 118 mmol/L (normal range at rest: 136-145 mmol/L), which classified him as being severely hyponatremic. Based on subsequent follow-up testing, this young tennis player likely also incurred a sweat-induced sodium deficit during this incident from the previous match, given his characteristically high sweating rate and sweat sodium concentration. The precise mechanism underlying hyponatremia is somewhat unclear, trought on by extensive sweating followed by ingesting low-sodium or sodium-free fluids (e.g., water) at a high rate for several hours or more. This can easily happen in tennis, particularly when playing multiple, long matches on successive days in the heat. Compared to marathons, triathlons, and other ultra-endurance events, the reported incidence of hyponatremia in tennis is very low. Still, with some mild cases of hyponatremia, a player might only experience fatigue, apathy, slight nausea, and a headache. These symptoms are not uncommon with players during a hot-weather tournament. Hyponatremia is a dangerous and potential threat to all tennis players - it`s seriousness and probability should not be overlooked or underestimated. Regular exercise and adequate calcium intake are important for normal growth and bone development in all girls and young women, and can be critical parts of an effective strategy to help prevent osteoporosis later in life. Generally, exercise (particularly weight-bearing exercise) has been considered to be beneficial for maximizing bone strength and density. However, we have shown that young healthy women, who were on a controlled diet, had significant sweat calcium losses and relatively high urinary calcium excretion, during a period of exercise in the heat. Further research revealed that adolescent girls had similar sweat calcium losses during tennis training and, for some, there was elevated bone turnover on those days that may have favored bone resorption (breakdown). Tennis, and other forms of popular exercise (characterized by extensive sweating), may induce calcium losses that could effectively "offset" some of the otherwise beneficial effects of exercise specific to bone health. Therefore, the dietary calcium requirement for such athletes may be somewhat higher than is currently recommended, especially during periods of extensive training and competition in the heat. Heat stress can not only diminish on-court performance - it can threaten a player`s health and safety. Unfortunately, to date, there are no data that accurately describe young tennis players` thermoregulatory balance, as indicated by core temperature, while playing tennis or training in hot and humid conditions. Moreover, it is also not known if high core body temperatures are more likely to occur in those players that are not well-hydrated prior to play and/or do not manage fluid intake appropriately during play. From a new study (currently in progress) we hope to provide novel insight to understanding the causes and degree of heat strain that junior tennis players experience during tournament play and training in hot and humid conditions. Our early results have already demonstrated dramatic differences in core body temperature when players maintain fluid intake at a rate that matches sweat output, versus comparable players that do not. These preliminary data emphasize the potential risk for excessive body heat retention during tennis, especially when fluid intake is less than optimal.